Analisa Pengaruh Pemodelan Jaringan EBGP dan IBGP Terhadap QoS Multimedia - Fajar Kurniawan; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Today, internet has become a part of everyday life for millennial society. An internet network addressing protocol is needed in order to connect one user to another user. Border Gateway Protocol (BGP) is a standard routing protocol offered to choose interdomain paths. The main function of BGP is to exchange network coverage information between BGP routers and other BGP routers. BGP is also divided into 2 types, the External Border Gateway Protocol (EBGP) and the Internal Border Gateway Protocol (IBGP). GNS3 is used to design and simulate modeling the BGP protocol and capturing the data packets using wireshark. The results obtained from the measurement of Quality of Service (QoS) for multimedia traffic in the EBGP and IBGP networks are 55 ms delay (EBGP) and 82.5 ms (IBGP) for audio streaming. Meanwhile the throughput value is 1.182 Mbit/sec (EBGP) and 0.591 Mbit/sec (IBGP) for audio streaming. These results show the good performance is reached because the result meet both ITU-T G.114 and ITU-T G.1010 standards, which is a good average delay for sending packet data is <150 ms and packet loss is <1%. Keywords : Network, EBGP, IBGP, QoS, Delay